On some new generalizations of Nadler contraction in b-metric spaces. Issue 1 (1st January 2020) - Zoran D., Mitrović; Parvaneh, Vahid; Mlaiki, Nabil; Hussain, Nawab; Radenović, Stojan
Abstract: We introduce some generalizations of contractions for multi-valued mappings and establish some fixed point theorems for multi-valued mappings in b -metric spaces. Our results generalize and extend several known results in b -metric spaces. Some examples are included which illustrate the cases when new results can be applied while old ones cannot.